1990
DOI: 10.1099/00221287-136-2-337
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a common enterobacterial flagellin epitope with a monoclonal antibody

Abstract: A monoclonal antibody (mAb), designated 15D8, was produced from BALB/c splenocytes of mice injected with Escherichiu coli flagella. ELISA of motile cells, non-motile cells and partially purified flagellin proteins showed that the mAb reacted specifically with flagella of E coli and with other members of the family Enterobacteriaceae. Western immunoblot analyses of enterobacterial flagella or cell extracts demonstrated that the antibody reacted with a single protein species in the extracts which was identical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Significant variation in flagellin Mr has also been observed for these enteric organisms (21). Cross-reactivity between the B. bronchiseptica flagellins and a monoclonal antibody (15D8) that recognizes enterobacterial flagellins (12) bronchiseptica. Interestingly, nicotinic acid did not induce motility in the strains we examined, although this signal has been shown to decrease production of dermonecrotic toxin in other B. avium isolates (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant variation in flagellin Mr has also been observed for these enteric organisms (21). Cross-reactivity between the B. bronchiseptica flagellins and a monoclonal antibody (15D8) that recognizes enterobacterial flagellins (12) bronchiseptica. Interestingly, nicotinic acid did not induce motility in the strains we examined, although this signal has been shown to decrease production of dermonecrotic toxin in other B. avium isolates (14).…”
Section: Methodsmentioning
confidence: 99%
“…Further evidence is provided in Fig. 6, which shows a Western blot demonstrating recognition of the B. bronchiseptica flagellins by a monoclonal antibody (15D8) that specifically recognizes a conserved epitope in flagellins expressed by E. coli and other members of the family Enterobactenaceae (12) (Fig. 6, lanes 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…Product samples, recFLA from S. Typhimurium, and LPS preparations from E. coli K-12 were subjected to sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) analysis with 10% polyacrylamide minigels (Invitrogen) under denaturing conditions. The separated proteins were electroblotted onto polyvinlyidene difluoride membranes (pore size, 0.45 m; Invitrogen) and were then incubated with anti-E. coli flagellin MAb (MAb 15D8; 1:1,000; Bioveris, Gaithersburg, MD) (5,18,22), followed by incubation with goat anti-mouse IgG (H烯L)-horseradish peroxidase conjugate (1: 5,000; ZyMax; Invitrogen). Immunodetection was revealed with an ECL Plus chemiluminescent detection system, according to the manufacturer's instructions (GE Healthcare UK Ltd., Buckinghamshire, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether the TLR5 ligand in sample B was indeed flagellin, a Western blot was performed with an antiflagellin-specific antibody (MAb 15D18) which has been shown to recognize an epitope in the flagellins of flagellated E. coli and S. Typhimurium (5,18,22). Flagellin has a known molecular mass of 40 to 60 kDa, depending on the bacterial species and strains of origin (6,18,20).…”
Section: Vol 47 2009 Tlrs Identify Molecular Microbial Impurity In mentioning
confidence: 99%
“…Sequencing of about 310 bases, starting at 130 bases upstream and extending to 180 bases downstream of the initiation codon, showed that the nucleotide base sequences of Proteins fractionated on SDS-PAGE were electrophoretically transferred onto nitrocellulose paper by K'estern blotting and probed by a described protocol (Feng e t al., 1990b) with an affinity-purified rabbit antibody to G U D obtained from M. \Yolcott and P. A. Hartman, Iowa State University, Ames, USA. Antigen-bound antibody on the nitrocellulose blot was detected by using goat anti-rabbit antibody conjugated with horseradish peroxidase (Kirkegaard & Perry Laboratories) and with the precipitable peroxidase substrate 4-chloro-1 -naphthol (BioRad) (Feng et al, 1990b).…”
Section: Sequencing and Analysis Of The Regulatory And 5' Regionmentioning
confidence: 99%